2008
DOI: 10.1007/s11218-008-9069-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial environment and affective outcomes in technology-rich classrooms: testing a causal model

Abstract: Research investigated classroom environment antecedent variables and student affective outcomes in Australian high schools. The Technology-Rich Outcomes-Focused Learning Environment Inventory (TROFLEI) was used to assess 10 classroom environment dimensions: student cohesiveness, teacher support, involvement, investigation, task orientation, cooperation, equity, differentiation, computer usage and young adult ethos. A sample of 4,146 high school students from Western Australia and Tasmania responded to the TROF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 42 publications
2
40
0
2
Order By: Relevance
“…This will improve student outcomes (Dorman, Fraser, Dorman, & Fraser, 2009) allow for constructing new competencies, beliefs, and personal empowerment student aptitude important as a teacher in the future. The unique environment of the educational 3D creations allows and invites the construction of knowledge and thinking about creative action or concrete guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…This will improve student outcomes (Dorman, Fraser, Dorman, & Fraser, 2009) allow for constructing new competencies, beliefs, and personal empowerment student aptitude important as a teacher in the future. The unique environment of the educational 3D creations allows and invites the construction of knowledge and thinking about creative action or concrete guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars see students' participation in online courses as the expression of over-involvement and commitment in the context of the course contents (Dorman & Fraser, 2009). …”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Results of previous studies have consistently shown that the learning environment affect students' academic self-efficacy and students' self-efficacy beliefs in academic performance and affect the improvement of learning environment and students' achievement (Velayutham & Aldrige, 2013). Dorman and Fraser (2009) stated that improvement of the classroom learning environment has the potential to improve students' outcomes. Students will learn better when they perceives that their classroom environment positively.…”
Section: Introductionmentioning
confidence: 99%